Characterization of a dimer preparation method for nanoscale organic aerosol. Issue 9 (2nd September 2019) - Rothfuss, Nicholas E.; Petters, Sarah S.; Champion, Wyatt M.; Grieshop, Andrew P.; Petters, Markus D.
Abstract: Nanoscale dimers have application in studies of aerosol physicochemical properties such as aerosol viscosity. These particle dimers can be synthesized using the dual tandem differential mobility analyzer (DTDMA) technique, wherein oppositely charged particle streams coagulate to form dimers that can be isolated using electrostatic filtration. Although some characterization of the technique has been published, a detailed thesis on the modes and theory of operation has remained outside the scope of prior work. Here, we present new experimental data characterizing the output DTDMA size distribution and the physical processes underlying its apparent modes. Key experimental limitations for both general applications and for viscosity measurements are identified and quantified in six distinct types of DTDMA experiments. The primary consideration is the production of an adequate number of dimers, which typically requires high mobility-selected number concentration in the range 25, 000–100, 000 cm −3 . The requisite concentration threshold depends upon the rate of spontaneous monomer decharging, which arises predominately from interactions of the aerosol with ionizing radiation within the coagulation chamber and is instrument location dependent. Lead shielding of the coagulation chamber reduced the first-order decharging constant from ∼2.0 × 10 −5 s −1 to ∼0.8 × 10 −5 s −1 in our laboratory. Dimer production at monomer diameters less than 40 nm is hindered by low bipolar charging efficiency. Results from the characterization experiments shed light on design considerations for general applications and for characterization of viscous aerosol phase transitions. Copyright © 2019 American Association for Aerosol Research